Agronegócios vs pequenos proprietários rurais: diferentes formas de conceber e lidar com os processos produtivos no campo: Presidente Olegário - MG (1990-2013) - Rodrigues, Leonardo dos Santos (2014)
This essay aims to analyze experiences of rural smallholders from Presidente Olegário, at northwest of Minas Gerais, that, between 1990 and 2003, exchanged they source of income by agriculture to milk livestock. They are farmers from the communities by Lobeira, Capoeirão dos Badús and Três Barras whose hand labor used is mainly homelike, that survive, nowadays, by saling milk to dairies. We attempted to follow the trajectory of these subjects that, until certain time, they obtained their income from agriculture, but now survive mainly of dairy farming; to characterize the effect of this change in their routine and establish the relationship between changes in this space and chronological cut and restricted the activities of representatives of \"agribusiness\". The work also involves discussion of concepts such as \"family farms\", \"agribusiness\", \"small farm\", \"small farmer\", \"farmer\", \"farmer\" etc.. which refer to different ways of living and refer to productive processes in the field. The \"family\" category, for example, seems crucial for the kind of skilled labor employed in the properties, and they are home to the families who live there and produce. Finally, it broadens the discussion with questions such as the relationship between the state and agrarian structure; the various perspectives of production and relationship with the land attached to different sectors and social groups; and clashes between different ways of conceiving the field work and the relationship with the land.